The imaginary audience and the personal fable in relation to risk behavior and risk perception during adolescence - Galanaki, Evangelia (Psychology: the Journal of the Hellenic Psychological Society, 2001)
The aim of the present study was to investigate the two main manifestations of adolescent egocentrism, that is, the imaginary audience and the personal fable, in relation to the frequency of risk behavior and risk perception. The contribution of this study is the empirical test of Elkind's Piagetian formulation (1967, 1978) about the relation between these factors, for the first time in a broad age range, with most of the existing egocentrism instruments, and for a variety of risk behaviors. ln a sample of 297 Greek adolescents 11-18 years old it was found that only certain dimensions of the personal fable had a positive correlation with the frequency of risk behavior and a negative correlation with risk perception. Contrary to our prediction, the imaginary audience in the form of heightened self-consciousness had a negative correlation with the frequency of risk behavior. Age and gender differences were also found. The limitations set by the somewhat low reliability of some egocentrism instruments are discussed, as well as a broader multivariate interpretation of adolescent risk-taking behavior, part of which is egocentrism. Finally, the implications of the results for health education programs are presented.